Elevated expression of galectin-3 in excessive scars: A pilot study - Victor Freire Salomão Ferreira; Felipe Simões Lemos; Roberto Stefan de Almeida Ribeiro; Silvio Renan Pinheiro Victor de-Araújo; Fabio Santiago Figueredo; Maria Lidia de Abreu Silva; Felipe Leite de-Oliveira; Thaís Porto Amadeu (Revista Brasileira de Cirurgia Plástica)
Introduction: Hypertrophic scars and keloids are types of excessive scars from abnormal skin healing. Galectin-3 (gal-3) is a protein from the lectin family capable of identifying carbohydrates, which can combine and act on different molecules. In the literature, the action of gal-3 as the main regulatory agent of fibrogenesis has already been described and is currently used in anti-fibrotic therapy for various organs such as the lung and liver. The objective of this pilot study was to show preliminary results found in the expression of gal-3 in exacerbated scars. Method: Twenty biopsy samples from excessive scars (16 keloids and 4 hypertrophic scars) and 9 samples from normal scars were collected from 22 women and 7 men. These samples were processed for routine histopathological analysis by immunohistochemistry to detect gal-3. Gal-3 positive cells were quantified by the stereological method using a 36-point grid. Results: Immunohistochemistry showed high expression of gal-3 in endothelial and epithelial cells of all scar samples, as well as expression in cells distributed throughout the dermis. Higher gal-3 expression was found in keloid samples (28% positive cells) compared to normal (18%) and hypertrophic (22%) scars (p = 0.0075). The results were obtained from a small number of patients, as this was a pilot study. Conclusion: The data suggest that gal-3 participates in the healing process and, due to its greater presence in keloid samples, it may be a potential biomarker for keloid formation and a promising therapeutic target to be explored.